Biocultural importance and conservation strategies for native maize in San Juan Yautepec-Nñantde Bótda, Mexico. - Casimiro- Hermenegildo , Laura Patricia; Pedraza-Mandujano, Joel; Albino-Garduño, Rocio; Estrada- Martínez, Emma; Santiago-Mejía, Horacio; Gómez-Ortiz, Yuriana; Ortega-Paczka , Rafael (Agricultura, Sociedad y Desarrollo, 2025)
Biocultural importance refers to the meaning or value that a human group assigns to the link between nature and culture, in time and space. The objective was to analyze the biocultural importance of native maize in San Juan Yautepec- Nñantde Bótda, in order to formulate conservation strategies. Research was carried out in San Juan Yautepec, Huixquilucan, State of Mexico, through participatory research, from December 2022 to February 2024. Maize was collected and ethnotaxa were identified. Seventeen in-depth interviews were conducted with peasants. Note was taken of the Food Security Index (FSI) and maize dishes. Two participatory workshops were held to document the work calendar and identify conservation strategies. The community’s “white” maize (Ma t´si taxka dethö) pertains to the Chalqueño species or cream-colored group, and the “blue” maize (Ma t´si modijä) pertains to the Elotes Chalqueños sub-species; their Otomi names indicate respect for maize. We classified prepared foods as either every day, festive or survival cooking. According to the FSI, only three families are self-sufficient in maize; however, peasants continue to plant maize for reasons of taste and identity. The current calendar of maize tasks consists of 27 cultural and agricultural activities. Due to the importance of maize, the community proposed 16 groups of conservation proposals; one of these was the Maize Fair, where 11 activities focused on its revaluation were implemented.